Evaluasi Jumlah Total Bakteri dan Staphylococcus aureus pada Produk Ayam Olahan dengan Pembelian Online - Pelangi Ananda Juandini; Deden Zamzam Badruzzaman; Eulis Tanti Marlina (Unpad Press, 2021)
Chicken meat is one of the basic ingredients of food that is preferred by the community because of its high nutrition and affordable prices. However, this high nutrition causes chicken meat to be easily contaminated with microorganisms, so it is necessary to process it with good sanitation so as to reduce the possibility of meat being contaminated by microorganisms and can be consumed healthily. This study aims to determine the process of implementing sanitation in the catering DM and to find out the total number of bacteria and Staphylococcus aureus in fried chicken and processed grilled chicken in DM catering. The results showed that the total number of bacteria in fried chicken was 1,57 x 106 < µ < 2,66 x 106 cfu/g, while in grilled chicken 1,74 x 106 < µ < 2,59 x 106 cfu/g, the results of the analysis of the calculation of the total number of S. aureus bacteria in fried chicken is 4,9 x 101 < µ < 7,1 x 101 cfu/g while for grilled chicken it is 5,1 x 101 < µ < 7,6 x 101 cfu/g. From these results it can be concluded that the total number of bacteria in DM catering exceeds the maximum limit. has been determined by BPOM but the total number of S. aureus bacteria in DM catering is still below the limit set by BPOM.